Coming of age in 2020 : teenagers on the year that changed everything - Schulten, Katherine (W. W. Norton & Company, Inc., 2022)
"A compilation of creative responses from teenagers-essays, poetry, cartoons, drawings, et al.-to the events of 2020 including but not limited to the pandemic, the election, and the Black Lives Matter protests"--